Impact of the Virtual Reality Mirror in Indian Retail Stores - Iyer, Aditya (The journal of contemporary issues in business and government, 2021)
The research paper focuses on the impact of Virtual Reality Mirror on the Indian retail store, which is dependent on functions such as user experience, purchasing decision and demographic variables. The user experience is dependent on the immersive experience like VR mirror and the average time spent for the trial of clothes. The purchasing decision is dependent on look and feel of fabric, long queues in stores and average shopping time. The demographic variables used in the research are age and gender. A qualitative interview with an experiential store manager was conducted to get insights about the impact of immersive technologies on the retail industry. A survey was also conducted to gather the above-mentioned variables and trends were plotted graphically which depicted demographic sectors that can be targeted by retail stores to increase sales.